Glass composition with low expansion coefficient
By using a glass composition with a low coefficient of thermal expansion designed with specific components, the problem of high thermal expansion coefficient of glass fiber is solved, and glass fiber with low dielectric constant and high elastic modulus is achieved, which is suitable for high-frequency and high-speed signal transmission and mass production, and meets the requirements of high-end circuit boards.
Patent Information
- Application Number
- CN202512016646.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-03-17
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of glass, in particular to a low-expansion coefficient glass composition. BACKGROUND
[0002] Glass fiber is widely used as a reinforcing material for resin-based composite materials, and such reinforcing materials are widely used in the fields of navigation, aerospace and electronic information. In order to meet the development of lightweight and miniaturization of portable electronic products, printed circuit boards are often designed to be more compact and complex, and more heat is generated during processing and service. The greater the difference in the expansion coefficients of the printed circuit board and electronic components, the greater the stress residual in the product and the greater the adverse effects on the components. Higher requirements are also placed on the stiffness of thin laminated circuit boards.
[0003] Glass fiber is usually manufactured in the following way: the corresponding weights of various glass raw materials are weighed according to the design ratio, mixed uniformly, and then put into a glass kiln to melt into a homogeneous glass liquid. The glass liquid is sprayed from a bushing with a special-shaped nozzle, and the high-temperature glass liquid is cooled and hardened to form a specific diameter of fiber-shaped glass while being stretched at high speed. The bushing is formed of noble metals such as platinum and rhodium.
[0004] Traditional E-Glass (electrical) is mainly composed of SiO2, Al2O3, CaO, B2O3, etc., and the content of alkali metal oxides in its composition is low to ensure its good electrical properties, chemical stability and anti-aging performance. E-Glass is often used as a reinforcing material to combine with resin to form a glass fiber reinforced composite material. The expansion coefficient of traditional E-Glass is as high as 54×10 -7 / ℃, which is quite different from the expansion coefficient of elements such as copper foil and semiconductor chips. The defects such as internal warping and stress of the multilayer board caused by the large difference in expansion coefficient will deteriorate the geometric shape and impedance stability of the precision circuit, making it difficult to meet the requirements of high-end circuit boards. In contrast, D-glass (dielectric) is a borosilicate glass fiber with low dielectric constant, which has a high SiO2 content to meet the needs of high-frequency and high-speed electronic circuits. S-glass (strength) belongs to the magnesium alumino-silicate glass system, and by increasing the SiO2 content and optimizing the proportion of components such as MgO and Al2O3, the glass network structure is made more dense and strong, thereby obtaining high strength and modulus. The expansion coefficients of D-glass and S-glass can reach 30×10 -7 / ℃ and 28×10 -7 / ℃. But D-glass has a high melting difficulty and a large viscosity due to SiO2, Al2O3 and B2O3 exceeding 90%, and cannot produce glass fibers below 7 μm, which also limits its application in thin circuit boards. S-glass reduces the expansion coefficient and viscosity by adjusting the formula, but the forming viscosity of the glass is still large, which cannot meet the stable production of large quantities. At the same time, in order to ensure the speed and quality of signal transmission, the printed circuit board needs to have low expansion coefficient and low forming viscosity, and also needs to have low dielectric constant and dielectric loss.
[0005] Therefore, it is urgent to develop a glass fiber with a lower thermal expansion coefficient, while having better batch production performance, and meeting the requirements of high frequency and high speed signal transmission. SUMMARY
[0006] The purpose of the present application is to provide a glass composition with low expansion coefficient, low dielectric constant, low dielectric loss and high elastic modulus, and also with good processability to meet the performance and scale production requirements.
[0007] In view of the above defects of the prior art, the present application provides a low expansion coefficient glass composition comprising the following components in the following amounts: 60 wt.%~70 wt.% SiO2, 16 wt.%~25 wt.% Al2O3, 0.6 wt.%~4.8 wt.% B2O3, 6.5 wt.%~10.5 wt.% MgO, 0~3 wt.% CaO, 0.01 wt.%~3 wt.% fluxing agent, 0.01 wt.%~0.5 wt.% fining agent; The sum of the mass percentages of the above components is 100 wt.%; wherein 51 wt.%≤SiO2+B2O3+Al2O3≤86 wt.%; the content of Al2O3 is denoted as A, the content of B2O3 is denoted as B, the content of MgO is denoted as M, and the content of CaO is denoted as C, then X=(2.48M+1.78C) / (1.96A+2.87B) is satisfied, and the value of X ranges from 0.35 to 0.55.
[0008] Preferably, the low expansion coefficient glass composition comprises the following components in the following amounts: 61 wt.%~69 wt.% SiO2, 17 wt.%~24 wt.% Al2O3, 1 wt.%~4.5 wt.% B2O3, 7 wt.%~10 wt.% MgO, 0.1 wt.%~2.8 wt.% CaO.
[0009] More preferably, the low coefficient of thermal expansion glass composition comprises the following components in the following amounts: 62 wt.%~68 wt.% SiO2, 19 wt.%~23 wt.% Al2O3, 1.8 wt.%~3.5 wt.% B2O3, 7.5 wt.%~9.5 wt.% MgO, and 0.2 wt.%~2.5 wt.% CaO.
[0010] Preferably, in the low coefficient of thermal expansion glass composition, 75 wt.% ≤ SiO2 + B2O3 + Al2O3 ≤ 85 wt.%.
[0011] Preferably, the flux comprises 0~1.5 wt.% Li2O, 0~1.5 wt.% Na2O, 0~0.3 wt.% TiO2, 0~0.3 wt.% Y2O3, and 0~0.3 wt.% La2O3; wherein 0≤Li2O+Na2O≤1.5 wt.%.
[0012] More preferably, in the low expansion coefficient glass composition, 10 wt.% ≤ MgO + CaO + Li2O + Na2O ≤ 44 wt.%.
[0013] Furthermore, in the low expansion coefficient glass composition, 11 wt.% ≤ MgO+CaO+Li2O+Na2O ≤ 19 wt.% or 35 wt.% ≤ MgO+CaO+Li2O+Na2O ≤ 42 wt.%.
[0014] Preferably, the clarifying agent includes at least one of SnO2, Sb2O3, CeO2, and fluoride clarifying agents.
[0015] Preferably, the content of the clarifying agent is 0.05 wt.% to 0.4 wt.%.
[0016] More preferably, the content of the clarifying agent is 0.1 wt.% to 0.3 wt.%.
[0017] Based on achieving the objectives of this invention, optimized parameters can further balance service performance and process performance. For example, they can balance elastic modulus and coefficient of thermal expansion, while also satisfying a certain viscosity-temperature curve, thus avoiding problems such as poor batch production stability caused by an excessively narrow controllable range in the wire drawing process.
[0018] The low-expansion coefficient glass composition designed with the component content of this invention has excellent mass production performance and can be produced using conventional glass manufacturing processes without the need for specialized equipment. For example, those skilled in the art can weigh various raw materials according to the above formula ratio, mix them uniformly, and then put them into a furnace to melt at 1550~1650 °C to form molten glass. Then, the glass can be cast into glass products of the target thickness (e.g., 20~30 mm) using a casting method. After annealing, the homogeneous glass can be drawn into fibers to prepare low-expansion coefficient glass composition into low-expansion high-modulus glass fibers for use in the manufacture of printed circuit boards and electronic components.
[0019] The sources of the aforementioned raw materials are diverse. For example, SiO2 can be sourced from quartz sand; Al2O3 from Al2O3 or Al(OH)3; B2O3 from boric acid, boric anhydride, or boromagnesite; MgO from MgO, MgCO3, or Mg(OH)2; CaO from CaO or CaCO3; Na2O from Na2CO3 or NaNO3; Li2O from Li2CO3 or LiNO3; Y2O3 from Y2O3; TiO2 from TiO2; and La2O3 from La2O3. Those skilled in the art can select the appropriate source based on actual production conditions or requirements.
[0020] Based on the above technical solutions, the component design concept and principle of the present invention are as follows: SiO2 is an important glass network forging agent, forming the glass network framework with [SiO4] tetrahedral basic structural units. Al2O3 is an important glass network intermediate, which can either connect [AlO4] tetrahedral structural units to [SiO4] tetrahedra to make the glass network denser, or fill the gaps in the [SiO4] network structure with [AlO6] octahedral structural units. SiO2 and Al2O3 are the main components of the glass network forging agent in this invention. Controlling the sum of SiO2 and Al2O3 contents within the design range can provide both a lower coefficient of thermal expansion and a high-frequency dielectric constant, while also satisfying the economic requirements of melting.
[0021] B2O3 is an important glass network aggregator, primarily existing in the form of [BO3]trigonometric bodies and [BO4] tetrahedra within the glass network. If it exists as a [BO4] tetrahedron, it will connect with [SiO4] and integrate into the glass network; if it exists as a [BO3]trigonometric body, it carries a negative charge and will cause the original glass network to depolymerize. As a secondary component of the glass network aggregator in this invention, the introduction of B2O3 in a designed proportion can reduce the overall polarizability of the glass composition, effectively ensuring low dielectric loss at high frequencies.
[0022] MgO and CaO are alkaline earth metal oxides and important exosomes in glass networks. They fill the gaps in the glass network with [MgO6] and [CaO6] octahedra, and to a certain extent, promote the transformation of [AlO6] to [AlO4] and [BO3] to [BO4], making the glass network denser. This invention introduces MgO and CaO, which not only effectively increases the elastic modulus of the glass composition but also promotes the content of [AlO4] and [BO4].
[0023] Li₂O and Na₂O, as alkali metal compounds, exist in the gaps of the glass network in an ionic state, disrupting the glass network structure. However, as alkali metal fluxes, when added in small amounts at the designed ratio, Li₂O and Na₂O can significantly reduce viscosity at high temperatures without causing significant degradation of high-frequency dielectric losses.
[0024] Y₂O₃, TiO₂, and La₂O₃ are all network exosomes, existing in the gaps of the glass network with a six-coordinate structure. As fluxes, Y₂O₃, TiO₂, and La₂O₃ can reduce the high-temperature viscosity of glass, which is beneficial for lowering the drawing temperature of glass fibers. When added in small amounts, they can also accumulate, further increasing the compactness of the glass network structure.
[0025] SnO2, Sb2O3, CeO2, and fluorides are used as clarifying agents. Fluorides, which can be introduced from AlF3, MgF2, or CaF2, greatly promote the removal of bubbles from the glass melt. This reduces the difficulty of bubble removal in the glass composition, resulting in a homogeneous, bubble-free glass melt free of segregation, and facilitating stable production control.
[0026] The core of the glass composition in this invention lies in the design of its components and the control of their content. Specifically, the contents of Al₂O₃, B₂O₃, MgO, and CaO satisfy the formula X = (2.48M + 1.78C) / (1.96A + 2.87B). This design promotes the transformation of Al and B into tetracoordinates, resulting in a denser glass network and giving the glass composition a low coefficient of thermal expansion, a low dielectric constant, and a high elastic modulus. Secondly, in the selection of fluxes, TiO₂, Y₂O₃, and La₂O₃ are used, supplemented with small amounts of Li₂O and Na₂O, to reduce the glass fiber drawing temperature, maintain low dielectric tangent loss, and further improve the elastic modulus. Furthermore, the glass composition of this invention does not contain As₂O₃ or iron oxides (Fe₂O₃). x O y Heavy metal oxides such as ) can effectively extend the service life of platinum-rhodium alloy materials (derived from the sprue material, where homogeneous molten glass flows out through the sprue before being drawn into glass fibers), thereby reducing production costs.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention provides a glass composition with a low coefficient of thermal expansion. Based on the design and content control of specific components, a dense glass network is formed, which enables the glass composition to have a low coefficient of thermal expansion, a low dielectric constant, and a high elastic modulus, while also taking into account mass production performance. In practical use, it meets the requirements of high-frequency and high-speed signal transmission and has broad application prospects. Detailed Implementation
[0028] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0029] In the following examples, the low coefficient of thermal expansion glass composition was prepared using the following steps: Weigh out the various raw materials according to the formula ratio, mix them evenly, put them into the furnace, and melt them at 1550~1650 ℃ for more than 600 minutes to form glass liquid. Then, use the casting method to form glass products with a thickness of 20~30mm, and anneal them at 650 ℃ for 4 hours. The homogeneous glass is then drawn into fibers to obtain low expansion and high modulus glass fibers.
[0030] The main equipment, operating tools, and testing and characterization methods involved in the embodiments are as follows: Coefficient of thermal expansion: The coefficient of thermal expansion of the glass cylinders prepared in each example and comparative example was determined from 30 ℃ to 300 ℃ using a NERZSCH 402CL dilatometer. Before testing, the samples were processed into 6 mm × 50 mm cylinders, dried in an ultra-clean drying oven, and then left to stand at room temperature for more than 2 h before testing. The heating rate was 5 K / min.
[0031] Dielectric properties: The dielectric constant and dielectric loss tangent at 10 GHz were tested using an MS46122-20 GHz instrument at room temperature. Samples were required to have smooth, scratch-free surfaces and no internal defects such as striations, nodules, or bubbles.
[0032] Elastic modulus: The elastic modulus was tested using a Grindosonic MK7 instrument. The sample size was 90 mm × 30 mm × 0.7 mm.
[0033] Example 1 This embodiment provides a glass composition with a low coefficient of thermal expansion, the component contents of which are as follows: 65.50 wt.% SiO2, 21.00 wt.% Al2O3, 2.50 wt.% B2O3, 9.30 wt.% MgO, 0.30 wt.%CaO, 0 Li2O, 1.00 wt.% Na2O, 0 TiO2, 0.10 wt.% Y2O3, 0 La2O3, 0.30 wt.% SnO2, 0 Sb2O3, 0CeO2, 0 fluoride.
[0034] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.49.
[0035] The performance test results of the low expansion coefficient glass composition in this embodiment are shown in Table 1.
[0036] Table 1: Performance Test Results of Glass Compositions with Low Coefficient of Expansion
[0037] The above results demonstrate that the low expansion coefficient glass composition of this embodiment possesses excellent comprehensive performance and meets the parameter requirements of this invention.
[0038] Example 2 This embodiment provides a glass composition with a low coefficient of thermal expansion, the component contents of which are as follows: 67.00 wt.% SiO2, 20.00 wt.% Al2O3, 2.00 wt.% B2O3, 9.50 wt.% MgO, 0.10 wt.%CaO, 0.30 wt.% Li2O, 1.00 wt.% Na2O, 1.00 wt.% TiO2, 0 Y2O3, 0 La2O3, 0.10 wt.% SnO2, 0.10 wt.% Sb2O3, 0.20 wt.% CeO2, 0.50 wt.% fluoride.
[0039] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.53.
[0040] The performance test results of the low expansion coefficient glass composition in this embodiment are shown in Table 2.
[0041] Table 2: Performance test results of glass compositions with low coefficient of thermal expansion
[0042] The above results demonstrate that the low expansion coefficient glass composition of this embodiment possesses excellent comprehensive performance and meets the parameter requirements of this invention.
[0043] Example 3 This embodiment provides a glass composition with a low coefficient of thermal expansion, the component contents of which are as follows: 68.00 wt.% SiO2, 19.00 wt.% Al2O3, 1.80 wt.% B2O3, 8.00 wt.% MgO, 1.00 wt.%CaO, 0.10 wt.% Li2O, 0.40 wt.% Na2O, 0.11 wt.% TiO2, 0.05 wt.% Y2O3, 0.20 wt.%La2O3, 0.05 wt.% SnO2, 0.09 wt.% Sb2O3, 0.20 wt.% CeO2, 1.00 wt.% fluoride.
[0044] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.51.
[0045] The performance test results of the low expansion coefficient glass composition in this embodiment are shown in Table 3.
[0046] Table 3: Performance Test Results of Glass Compositions with Low Coefficient of Expansion
[0047] The above results demonstrate that the low expansion coefficient glass composition of this embodiment possesses excellent comprehensive performance and meets the parameter requirements of this invention.
[0048] Example 4 This embodiment provides a glass composition with a low coefficient of thermal expansion, the component contents of which are as follows: 63.00 wt.% SiO2, 23.00 wt.% Al2O3, 3.25 wt.% B2O3, 9.80 wt.% MgO, 0.20 wt.%CaO, 0 Li2O, 0.20 wt.% Na2O, 0 TiO2, 0 Y2O3, 0.15 wt.% La2O3, 0.20 wt.% SnO2, 0.05 wt.%Sb2O3, 0.05 wt.% CeO2, 0.10 wt.% fluoride.
[0049] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.45.
[0050] The performance test results of the low expansion coefficient glass composition in this embodiment are shown in Table 4.
[0051] Table 4: Performance Test Results of Glass Compositions with Low Coefficient of Expansion
[0052] The above results demonstrate that the low expansion coefficient glass composition of this embodiment possesses excellent comprehensive performance and meets the parameter requirements of this invention.
[0053] Example 5 This embodiment provides a glass composition with a low coefficient of thermal expansion, the component contents of which are as follows: 64.00 wt.% SiO2, 21.50 wt.% Al2O3, 3.50 wt.% B2O3, 7.00 wt.% MgO, 1.50 wt.%CaO, 0.20 wt.% Li2O, 0.20 wt.% Na2O, 0.10 wt.% TiO2, 0.10 wt.% Y2O3, 0.10 wt.%La2O3, 0.05 wt.% SnO2, 0.05 wt.% Sb2O3, 0.30 wt.% CeO2, 1.40 wt.% fluoride.
[0054] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.38.
[0055] The performance test results of the low expansion coefficient glass composition in this embodiment are shown in Table 5.
[0056] Table 5: Performance Test Results of Glass Compositions with Low Coefficient of Expansion
[0057] The above results demonstrate that the low expansion coefficient glass composition of this embodiment possesses excellent comprehensive performance and meets the parameter requirements of this invention.
[0058] Comparative Example 1 This comparative example provides a glass composition with the following component contents: 59.00 wt.% SiO2, 26.00 wt.% Al2O3, 1.00 wt.% B2O3, 12.00 wt.% MgO, 0.30wt.% CaO, 0 Li2O, 1.00 wt.% Na2O, 0.20 wt.% TiO2, 0 Y2O3, 0.20 wt.% La2O3, 0.10 wt.%SnO2, 0.10 wt.% Sb2O3, 0.10 wt.% CeO2, 0 fluoride.
[0059] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.56.
[0060] The performance test results of the glass compositions of the comparative examples are shown in Table 6.
[0061] Table 6: Performance Test Results of Glass Compositions
[0062] Comparative Example 2 This comparative example provides a glass composition with the following component contents: 70.00 wt.% SiO2, 15.00 wt.% Al2O3, 5.00 wt.% B2O3, 3.00 wt.% MgO, 0 CaO, 0Li2O, 2.50 wt.% Na2O, 0.80 wt.% TiO2, 3.00 wt.% Y2O3, 0.50 wt.% La2O3, 0 SnO2, 0.10 wt.% Sb2O3, 0.10 wt.% CeO2, 0 fluoride.
[0063] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.17.
[0064] The performance test results of the glass compositions of the comparative examples are shown in Table 7.
[0065] Table 7: Performance Test Results of Glass Compositions
[0066] Comparative Example 3 This comparative example provides a glass composition with the following component contents: 60.00 wt.% SiO2, 18.00 wt.% Al2O3, 4.00 wt.% B2O3, 8.00 wt.% MgO, 8.00 wt.%CaO, 0.10 wt.% Li2O, 0.90 wt.% Na2O, 0 TiO2, 0 Y2O3, 0 La2O3, 0 SnO2, 0 Sb2O3, 1.00 wt.%CeO2, 0 fluoride.
[0067] Where X = (2.48M + 1.78C) / (1.96A + 2.87B) = 0.73.
[0068] The performance test results of the glass compositions of the comparative examples are shown in Table 8.
[0069] Table 8: Performance Test Results of Glass Compositions
[0070] The test results from the embodiments and comparative examples of this invention show that, within the design range of this invention, the embodiments generally exhibit low coefficient of thermal expansion, low dielectric constant, low dielectric loss, and high elastic modulus, and possess excellent processing performance. In contrast, when X deviates from the design range of this invention, the overall performance of the comparative examples is inferior to that of the embodiments described above. This invention meets the requirements for high-frequency and high-speed signal transmission parameters and has broad application prospects in fields such as printed circuit board and electronic component fabrication.
[0071] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A low coefficient of expansion glass composition characterized in that, The components include the following contents: 60 wt.%~70 wt.% SiO2, 16 wt.%~25 wt.% Al2O3, 0.6 wt.%~4.8 wt.% B2O3, 6.5 wt.%~10.5 wt.% MgO, 0~3 wt.% CaO, 0.01 wt.%~3 wt.% fluxing agent, 0.01 wt.%~0.5 wt.% fining agent; The sum of the mass percentages of the above components is 100 wt.%; wherein, 51 wt.%≤SiO2+B2O3+Al2O3≤86 wt.%; the content of Al2O3 is denoted as A, the content of B2O3 is denoted as B, the content of MgO is denoted as M, and the content of CaO is denoted as C, then X=(2.48M+1.78C) / (1.96A+2.87B) is satisfied, and the value range of X is 0.35~0.
55.
2. The low coefficient of expansion glass composition according to claim 1, wherein The components include the following contents: 61 wt.%~69 wt.% SiO2, 17 wt.%~24 wt.% Al2O3, 1 wt.%~4.5 wt.% B2O3, 7 wt.%~10 wt.% MgO, 0.1 wt.%~2.8 wt.% CaO.
3. The low coefficient of expansion glass composition according to claim 2, wherein, The components include the following contents: 62 wt.%~68 wt.% SiO2, 19 wt.%~23 wt.% Al2O3, 1.8 wt.%~3.5 wt.% B2O3, 7.5 wt.%~9.5 wt.% MgO, 0.2 wt.%~2.5 wt.% CaO.
4. The low coefficient of expansion glass composition of claim 1, wherein: 75 wt.%≤SiO2+B2O3+Al2O3≤85 wt.%.
5. The low coefficient of expansion glass composition of claim 1, wherein: The fluxing agent includes 0~1.5 wt.% Li2O, 0~1.5 wt.% Na2O, 0~0.3 wt.% TiO2, 0~0.3 wt.% Y2O3, 0~0.3 wt.% La2O3; wherein, 0≤Li2O+Na2O≤1.5 wt.%.
6. The low coefficient of expansion glass composition of claim 5, wherein: 10 wt.%≤MgO+CaO+Li2O+Na2O≤44 wt.%.
7. The low coefficient of expansion glass composition of claim 6, wherein: 11 wt.%≤MgO+CaO+Li2O+Na2O≤19 wt.% or 35 wt.%≤MgO+CaO+Li2O+Na2O≤42 wt.%.
8. The low coefficient of expansion glass composition of claim 1, wherein: The fining agent includes at least one of SnO2, Sb2O3, CeO2, and a fluoride fining agent.
9. The low coefficient of expansion glass composition of claim 1, wherein: The content of the fining agent is 0.05 wt.%~0.4 wt.%.
10. The low coefficient of expansion glass composition of claim 1, wherein: The content of the fining agent is 0.1 wt.%~0.3 wt.%.